A new technique for FACTS devices placement via stability index-load tracing / Z. Hamid ...[et al.] - Hamidi, Z.S.; Musirin, I.; Othman, M. M.; Rahim, M. N. A. (UiTM Press, 2012)
Placement of shunt elements such as FACTS devices can be performed through various methods such as sensitivity analysis, optimization method, and the method that is rarely applied, termed as power tracing. Currently, the usage of power tracing technique is majorly limited to the field of transmission service pricing although there are various methods that have been developed by researchers. Because of that, this paper promotes a new technique for identifying the most suitable load bus to be selected for shunt element placement by means of Fast Voltage Stability Index Load Tracing (FVSI-LT) via a new hybrid algorithm, Blended Crossover Continuous Ant Colony Optimization (BX-CACO). Validation on IEEE 14 and 57-Bus RTS revealed that the proposed method has capability to be applied into real system.